2009
DOI: 10.1002/app.29818
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐crazed PET fibers imparting antibacterial activity by release of Zn2+

Abstract: Poly(ethylene terephthalate) fibers containing zinc chloride in the fiber bulk were prepared by solvent crazing. Fibers containing 6 g/Kg and 13 g/Kg Zn 2þ were investigated. SEM-EDX analyses and the formation of the pink bis(1,5-dithiocarbazonato-N,S) complex inside the fibers confirm the presence of zinc. UV-Vis spectroscopy indicates a slow release of zinc ions into the aqueous media and, thus, the fibers serve as a release system to inhibit the growth of Escherichia coli during the first exposure. Thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Therefore, polymer crazing in liquid media may be considered as a http://dx.doi.org/10.1016/j.eurpolymj.2015.03.003 0014-3057/Ó 2015 Elsevier Ltd. All rights reserved. method for obtaining nanoporous materials (membranes and sorbents) and as a process for producing nanocomposites and highly disperse polymer-polymer blends [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polymer crazing in liquid media may be considered as a http://dx.doi.org/10.1016/j.eurpolymj.2015.03.003 0014-3057/Ó 2015 Elsevier Ltd. All rights reserved. method for obtaining nanoporous materials (membranes and sorbents) and as a process for producing nanocomposites and highly disperse polymer-polymer blends [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The crazes that are generated because of bulk surface imperfections are usually heterogeneous and have an irregular distribution along the filament length. Weichold et al reported that during solvent crazing, the number and distribution of the crazes along the filament are random 16. Figures 2 and 3 show the typical photographs of the crazed surface and cross‐section of a filament, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Weichold et al reported that during solvent crazing, the number and distribution of the crazes along the filament are random. 16 Figures 2 and 3 show the typical photographs of the ARTICLE crazed surface and cross-section of a filament, respectively. As can be seen in Figure 3(b), there are periodic vertical dark lines in the filament structure.…”
Section: Structure Of the Crazed Filamentsmentioning
confidence: 99%
“…[32,33] At the same time, a component dissolved in the AAM is incorporated into the fibrillar-porous structure of crazes being formed. [34,35] Other approach to the preparation of nanocomposites is the synthesis of a second component in a nanoporous polymeric matrix preliminarily formed by the crazing mechanism. [36][37][38] In contrast to other methods used for the preparation of multicomponent materials, the proposed approach based on the phenomenon of crazing does not require the thermodynamic compatibility of the components and makes it possible to regulate the dispersity of a filler and the character of its distribution in a polymeric matrix within a wide range from the molecular and nanosized level of the dispersity of individual particles to the formation of continuous interpenetrating phases and layered structures.…”
Section: Composite Materialsmentioning
confidence: 99%
“…Mechanical stress applied to a polymer in the presence of an adsorption‐active medium (AAM) leads to the self‐dispersion of the polymer in the zones of local deformation (crazes) into oriented fibrils 5–20 nm in diameter, which are spatially separated by nanosized cavities; as a result, developed porosity (as high as 60 vol%) is created . At the same time, a component dissolved in the AAM is incorporated into the fibrillar‐porous structure of crazes being formed . Other approach to the preparation of nanocomposites is the synthesis of a second component in a nanoporous polymeric matrix preliminarily formed by the crazing mechanism .…”
Section: Introductionmentioning
confidence: 99%